SEASONAL VARIABILITY OF ATLANTIC WATER ON THE CONTINENTAL SLOPE OF THE LAPTEV SEA DURING 2002-2004 - Dmitrenko I.A.; Polyakov I.V.; Simmons H.L.; Ivanov V.V.; Kirillov S.A.; Timokhov L.A.; Walsh D. (My University, 2006)
2002-04 observations carried out on the Laptev Sea continental slope as part of the Nansen and Amundsen Basins Observational System (NABOS) project are used to study variations of the intermediate (150-800 m) Atlantic water (AW) layer of the Arctic Ocean. At the mooring site, AW exhibits seasonal changes, with higher/lower temperature and salinity in winter/summer. This variability is attributed to the shift of the AW core toward the slope in winter and away from the slope in summer. Seasonal variation of wind is among the possible factors governing seasonal changes of the AW layer. © 2006 Elsevier B.V. All rights reserved.
Keywords: ATLANTIC WATER LAYER; SEASONAL TEMPERATURE VARIATIONS; WIND